AFRICA AND PAX-AFRICANA IN THE AGE OF INTERVENTIONISM (Journal of Governance and Development (JGD), 2021)
This article, drawing data from library and online sources, examines and engages issues in Africa’s quest for pax-Africana in the age ofinterventionism. It notes that Africa’s quest for pax-Africana in the age of interventionism is undercut by many factors, chief amongwhich is the dependency and weaknesses of African states which always predispose extra-African powers to intervene in matters thatshould exclusively be handled by Africans. It concludes that as long as Africa remains trapped in dependent relations and the climate of disunity persists among African statesmen, its quest for pax-Africana would remain daunting.